Examining The Psychometric Properties Of The Deputy-principal Monitoring Questionaire - Roslizam Hassan; Lokman Mohd Tahir; Mohammed Borhandden Musah; Norazah Abdul Aziz; Lina Mursyidah Hamzah; Hanin Naziha Hasnor; Roslee Ahmad (IJERE, 2025)
Indexed by Scopus